2022
DOI: 10.3390/d14110977
|View full text |Cite
|
Sign up to set email alerts
|

New Botrylloides, Botryllus, and Symplegma (Ascidiacea: Styelidae) in Coral Reefs of the Southern Gulf of Mexico and Mexican Caribbean Sea

Abstract: Compound styelid ascidians are distributed in all marine environments and usually exhibit high morphological plasticity and complexity. In particular, Botrylloides, Botryllus, and Symplegma species show high morphological variations leading to confusion in traditional taxonomy assignments and to ambiguity in species delineation. Fewer than 20 species in these genera are registered in the Atlantic region. Here we surveyed the coral reefs of the southern Gulf of Mexico and Mexican Caribbean Sea, barcoded a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…The NCBI Blast analysis revealed that all samples from the present study exhibited a coverage above 99% with the B. humilis samples, which were referred to as Botryllus sp. hu in the NBCI record (Table S3, Palomino-Alvarez et al, 2022). The genetic distance between the Mexico samples and the present study samples was less than 1%, and a 1% distance was observed between the samples of the present study and the Israeli B. anceps sample (Fig.…”
Section: Resultsmentioning
confidence: 42%
See 1 more Smart Citation
“…The NCBI Blast analysis revealed that all samples from the present study exhibited a coverage above 99% with the B. humilis samples, which were referred to as Botryllus sp. hu in the NBCI record (Table S3, Palomino-Alvarez et al, 2022). The genetic distance between the Mexico samples and the present study samples was less than 1%, and a 1% distance was observed between the samples of the present study and the Israeli B. anceps sample (Fig.…”
Section: Resultsmentioning
confidence: 42%
“…However, the PTP analysis suggests the possibility of a distinct species in the Kızkalesi region. Previous studies have reported highlighted significant genetic differences (>10%) within botryllid ascidian species (Rocha et al, 2019;Palomino-Alvarez, 2022;Reem et al, 2022), underscoring the necessity for thorough morphological examinations to arrive at definitive conclusions regarding the species' classification. Until further examination is conducted, the possibility of two sister species should be considered; B. israeliense from the Tisan region and Botrylloides sp.…”
Section: Discussionmentioning
confidence: 99%
“…Ascidian species named after ascidiologists…and their loved ones. (a) Botryllus lambertorum , discovered and described by Marie Nydam, Lilian Palomino‐Alvarez, and Rosana Rocha, and dedicated to Gretchen and Charles Lambert (Palomino‐Alvarez et al, 2022). (b) Didemnum lambertae , discovered by Rosana Rocha (Rocha et al, 2015).…”
Section: Figurementioning
confidence: 99%
“…A Botryllus-only clade (Clade "a") is the sister clade to the rest of the ingroup, including both Botryllus and Botrylloides species (Figure 3 and Supplementary Figure 5). We were able to examine and describe the morphological characteristics of 4 of the 7 species forming Clade "a": Botryllus camur (Palomino-Alvarez et al, 2022), Botryllus bonanzus (Palomino-Alvarez et al, 2022), Botryllus primigenus B (Salonna et al, 2021), and Botryllus watanabei n. sp. (Supplementary File 2).…”
Section: Sample Identification Reveals a Hidden Botryllid Diversitymentioning
confidence: 99%